Factors Affecting Customer Satisfaction at Online Grocery - Abdullah, Abdullah; Rahmadhani, Sari (Lembaga Riset, Publikasi dan Konsultasi JONHARIONO, 2024)
This study aims to analyze customer satisfaction in shopping online. Customer activity in making online purchases is reviewed from the performance of the companies that serve, the safety of consumers in transactions, and the payment models offered by the company can affect satisfaction in making repeated purchases on online stores. The hypothesis test was carried out using data obtained from respondents who frequently shopped online in the last three years. Respondents were domiciled in the city of Semarang and obtained 164 questionnaires that could be processed by multiple linear regression analysis. The test results show that the company's performance in maintaining customer service satisfaction online is influenced by three important factors. First, there is a well-communicated customer service performance and quick response. Second, the availability of easy choice of transaction models that are well informed with customers. Third, in transactions, there is a guarantee of security of both data and transaction value, so that it can increase trust in both data and punctuality with customers.